2022
DOI: 10.1021/acs.jpcb.2c00340
|View full text |Cite
|
Sign up to set email alerts
|

Energy Landscapes for Base-Flipping in a Model DNA Duplex

Abstract: We explore the process of base-flipping for four central bases, adenine, guanine, cytosine, and thymine, in a deoxyribonucleic acid (DNA) duplex using the energy landscape perspective. NMR imino-proton exchange and fluorescence correlation spectroscopy studies have been used in previous experiments to obtain lifetimes for bases in paired and extrahelical states. However, the difference of almost 4 orders of magnitude in the base-flipping rates obtained by the two methods implies that they are exploring differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 185 publications
1
6
0
Order By: Relevance
“…The parallel stacking of the indole with A and T bases suggested that the dye might be “sandwiched” and trapped into stable microstates depending on the spatial arrangement of the T and A bases, leading to the different orientations observed for bTT and bAA . As dyes occasionally changed orientation, we speculated that the transition between stable microstates would be promoted by DNA breathing [ 33 , 63 ], base flipping [ 64 ], or a mechanism in which the dye and the neighboring bases stack and unstack.…”
Section: Resultsmentioning
confidence: 99%
“…The parallel stacking of the indole with A and T bases suggested that the dye might be “sandwiched” and trapped into stable microstates depending on the spatial arrangement of the T and A bases, leading to the different orientations observed for bTT and bAA . As dyes occasionally changed orientation, we speculated that the transition between stable microstates would be promoted by DNA breathing [ 33 , 63 ], base flipping [ 64 ], or a mechanism in which the dye and the neighboring bases stack and unstack.…”
Section: Resultsmentioning
confidence: 99%
“…Although the base flipping process is more frequently observed to proceed through the major groove in nucleic acids, it is not uncommon to observe purine nucleotides flipping via the minor groove pathway. 93,94 Tetraloop Adopts Conformations Conducive to Binding of the Reader Protein. A crystal structure of the A*UCG tetraloop bound to the reader (YTHDC1) protein shows that the tetraloop is recognized by the reader protein in a single-stranded conformation (Figure S10).…”
Section: ■ Resultsmentioning
confidence: 99%
“…The base flipping through the minor groove was due to a conformational change in the RNA tetraloop, which led to its opening (Figure S9). Although the base flipping process is more frequently observed to proceed through the major groove in nucleic acids, it is not uncommon to observe purine nucleotides flipping via the minor groove pathway. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lacking stabilizing RNAP interactions (and thus lacking a driving force for unstacking), t-strand bases may remain largely stacked in I1. Although the rates of interconversion between the I1 ensemble intermediates are unknown, they are likely relatively fast: in the absence of protein-DNA interactions, lifetimes of transiently open DNA bubbles (2-10 bp) 68 or extrahelical bases 69 range from 10 -2 to 10 -6 s. Because the MnO 4 - oxidation reaction rate constant is relatively slow (∼15 M - 1 s - 1 ) and decreases with decreasing temperature 70 , we suggest that the footprinting conditions (low temperature, low MnO 4 - dose) used for σP R may have prevented detection of DNA opening in I1.…”
Section: Discussionmentioning
confidence: 99%